THE STATUS OF SPECIES COMPOSITION AND BIOMASS OF ZOOBENTHOS IN LAN HA BAY, CAT BA ISLANDS - Dat, Dinh Thanh; Chieu, Hoang Dinh; Hoa, Luu Xuan (Vietnam Journal of Marine Science and Technology, 2016)
In July 2014, 15 coral reef areas were observed in Lan Ha bay, Cat Ba island. Research results showed that 210 benthic species belonging to 55 families, 22 orders of 3 phyla were recorded, including 114 Gastropoda species, 67 Bivalvia species, 27 Echinodermata species and 2 Arthropoda species. Amongst 210 benthic species, 4 species are listed in the Red Data Book of Vietnam. The low economic value species such as Barbatia lima, Septifer bilocularis were the most abundant whereas the high economic value species were least abundant. The distribution of benthic species in Lan Ha bay was not equal but depended on the type of coral reefs’ substrate and protected levels. The coral reefs in better protected condition support distribution of many benthic species in Van Boi, Cat Dua, Tai Keo, Gio Cung. Biodiversity of benthic species in the coral reefs in Lan Ha bay, Cat Ba islands are now under the threat csuding decline of species composition and especially the biomass. The estimation of present total biomass of some benthic species was quite high with 88 tons. Among them, the present total biomass of sea cucumber was 49.79%; black-lip pearl oyster was 91.01%; male trochus was 74.79% as compared to those in 2012.